Overlapping Authority In Judicial Oversight Komisi Yudisial V. Badan Pengawas Mahkamah Agung - Kenny Jesica (Talenta Publisher, Universitas Sumatera Utara, 2025)
Judicial oversight is a crucial element in maintaining the integrity and accountability of the judiciary in a state based on the rule of law. In Indonesia, this oversight function is carried out by two institutions namely Komisi Yudisial and Badan Pengawas Mahkamah Agung. However, their authority often overlaps, which not only gives rise to jurisdictional conflicts but also leads to institutional inefficiency and legal uncertainty. This study aims to analyze the authority of each institution based on laws and institutional practices, and to evaluate its impact on the effectiveness of the judicial oversight system. Using a normative and descriptive-analytical approach, this study finds that the unclear division of authority between Komisi Yudisial and Badan Pengawas Mahkamah Agung has hampered the oversight function, created waste of resources, and weakened public trust in the judiciary. This study recommends the need for inter-institutional harmonization of regulations or even restructuring of the judicial oversight institution to create a more efficient, integrated system that ensures legal certainty without sacrificing judicial independence.